Atención especializada para la inclusión educativa a niños con necesidades educativas especiales - Miranda Villamar, Carlos Tobías (2020)
This research work addresses issues inherent to educational inclusion and attention to diversity in the international context and with special attachment to the educational units run by the Armed Forces, for which a comparative analysis of the Latin American countries that have undertaken studies relevant about the performance of the military teacher in the training of children and youth. The educational inclusion and attention to diversity by the military teacher has been palpable for the lack of strategies, resources and didactic tools for attention to diversity in the development of the teaching-learning process of the military formality program, this situation It has been reflected by the different instruments applied to teachers, principals and students, in which it has been possible to observe the actions and difficulties of teachers towards children with special educational needs associated or not with a disability............